Cambodia : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. (Policy Papers; Policy Paper ;, 2005)
Cambodia is not a HIPC country because its debt levels were below the relevant thresholds. It is, however, eligible under the MDRI because it had per capita annual GDP of below USD 380 as of 2004. No IDA relief is currently expected under the MDRI for non-HIPC countries. Staff is of the view that all criteria have been met, and recommends that the Board determine that Cambodia qualifies for immediate relief under the MDRI.